Prophetic authority and intellectual humility: revisiting the palm pollination hadith in contemporary Islamic epistemology - Nazri, Mohd Arif; Zainan Nazri, Nurul Jannah; Zainan Nazri, Nurul Mukminah (NUN Gemilang Enterprise, Malaysia, 2025)
This article reexamines the oft-cited hadith concerning palm pollination (ta‘bir al-nakhl) and its misuse to confine the Prophet Muhammad’s authority to purely doctrinal or ritual matters. Through a textual analysis of the narrations in Sahih al-Bukhari and Sahih Muslim alongside commentaries by Ibn Hajar, al-Qadi ‘Iyad, and contemporary scholars such as Mufti Taqi Usmani, the study argues that the hadith does not support a compartmentalised understanding of Islam. Rather, it reflects the Prophet’s educational method in differentiating empirical experimentation from revelation, without diminishing his comprehensive authority (al-sultah al-shar‘iyyah al-kamilah). Misreading this hadith has led some modern thinkers to justify selective obedience to the Sunnah, particularly in economic and ethical matters such as riba. The paper concludes that true intellectual humility requires recognising the Prophet as the ultimate guide not only in creed and worship but also in moral and practical affairs.